Scenedesmus sp. ASK22 cultivation using simulated dairy wastewater for nutrient sequestration and biofuel production: insight into fuel properties and their blends - Pandey A.; Srivastava S.; Kumar S. (My University, 2025)
In this study, Scenedesmus sp. ASK22’s growth, lipid productivity and nutrient removal capacity were examined in indoor bench-scale and outdoor pilot-scale experiments using different culture media. The possibility of producing biodiesel from Scenedesmus sp. ASK22 was explored, and the physicochemical parameters of the biodiesel produced were compared to those of Indian petro-diesel. The findings revealed that in an indoor bench-scale culture, the maximal biomass concentration can approach 3.44 g L−1, when compared to the outdoor pilot-scale (2.09 g L−1), using nutrients supplemented simulated dairy effluent (NSDE) as a culture medium. Moreover, as compared to the BG11 medium, the cost of NSDE medium was ~3–4.7-fold lower. Maximum N-NO3−1, P-PO4−3 and chemical oxygen demand (COD) removal efficiency obtained in indoor culture conditions was 99.19%, 95.78% and 95.00%, respectively, compared to that of 95.10%, 84.87% and 92.50%, respectively, for outdoor conditions using NSDE as Scenedesmus sp. ASK22 culture medium. C16/C18 methyl esters make up most of the Scenedesmus sp. ASK22–derived biodiesel. Finally, the qualities of the produced biodiesel and blends were within the approved biodiesel standard specification, showing that Scenedesmus sp. ASK22 culture in dairy effluent has a lot of potential for scaling up for high-quality biodiesel production and dairy effluent treatment. The results demonstrated the potential of Scenedesmus sp. ASK22 to become feedstock of an integrated wastewater treatment and superior quality biodiesel production. Graphical abstract: [Figure not available: see fulltext.] © 2022, The Author(s), under exclusive licence to Springer-Verlag GmbH Germany, part of Springer Nature.